Looped energy harvester for human motion. (18th September 2017) - Geisler, M; Boisseau, S; Gasnier, P; Willemin, J; Gobbo, C; Despesse, G; Ait-Ali, I; Perraud, S
Abstract: The development of energy harvesters for smart wearables is a challenging topic, with a difficult combination of ergonomics constraints, lifetime and electrical requirements. In this work, we focus on an inertial inductive structure, composed of a magnetic ball circulating inside a closed-loop guide and converting the kinetic energy of the user's limbs into electricity during the run. A specific induction issue related to the free self-rotation of the ball is underlined and addressed using a ferromagnetic 'rail' component. From a 2 g moving ball, a 5 cm-diameter 21 cm 3 prototype generated up to 4.8 mW of average power when worn by someone running at 8 km h −1 . This device is demonstrated to charge a 2.4 V NiMH battery and supply an acceleration and temperature Wireless Sensor Node at 20 Hz.